Evaluation of an Objective MRI-Based Tumor Regression Grade (mrTRG) Score and a Subjective Likert Score for Assessing Treatment Response in Locally Advanced Rectal Cancers—A Retrospective Study - Katdare, Aparna N.; Baheti, Akshay D.; Pangarkar, Sayali Y.; Mistry, Kunal A.; Ankathi, Suman K.; Haria, Purvi D.; Choudhari, Amit J.; Guha, Amrita; Gala, Kunal; Shetty, Nitin; Kulkarni, Suyash; Ramadwar, Mukta; Bal, Munita (Indian Journal of Radiology and Imaging, 2023)
Purpose: Magnetic resonance imaging (MRI) with the help of MRI-based tumor regression grade (mrTRG) score has been used as a tool to predict pathological tumor regression grade (pTRG) in patients of rectal cancer post-neoadjuvant chemoradiation. Our study aims to evaluate the ability of MRI in assessing treatment response comparing an objective mrTRG score and a subjective Likert score, with a focus on the ability to predict pathologic complete response (pCR).Methods: Post-treatment MRI studies were retrospectively reviewed for 170 consecutive cases of histopathologically proven rectal cancer after receiving neoadjuvant chemoradiation and prior to surgery by two oncoradiologists blinded to the eventual postoperative histopathology findings. An objective (mrTRG) and a subjective Likert score were assigned to all the cases. Receiver operating characteristic curves were constructed to determine the ability of Likert scale and mrTRG to predict pCR, with postoperative histopathology being the gold standard. The optimal cutoff points on the scale of 1 to 5 were obtained for mrTRG and Likert scale with the greatest sum of sensitivity and specificity using the Youden Index.Results: The most accurate cutoff point for the mrTRG to predict complete response was 2.5 (using Youden index), with a sensitivity of 69.2%, specificity of 69.6%, positive predictive value (PPV) of 85.6%, negative predictive value (NPV) of 46.4%, and accuracy of 69.3%. The most accurate cutoff for the Likert scale to predict complete response was 3.5, with a sensitivity of 47.5%, specificity of 89.1%, PPV of 91.9%, NPV of 39.4%, and accuracy of 59%. mrTRG had a lower cutoff and was more accurate in predicting pCR compared to Likert score.Conclusion: An objective mrTRG was more accurate than a subjective Likert scale to predict complete response in our study.
Keywords: Likert; MRI; rectal cancer; TRG